Writing and script a very short introduction - Robinson, Andrew 1957- (Very short introductions, 2009)
Writing is a defining marker of civilisation; without it there could be no accumulation of knowledge. Andrew Robinson tells the fascinating story of the history of writing, considering its development, and examining the enormous variety of writing and scripts we use today